INTIMATE RELATIONSHIPS IN CONTEXT: STRESS SPILLOVER, RELATIONSHIP EFFICACY, AND RELATIONSHIP SATISFACTION - Bahun, Ivana; Huić, Aleksandra (Primenjena psihologija, 2017)
Recently, research has shown that stress experienced outside the relationship is negatively associated with relationship outcomes, such as relationship satisfaction. However, the exact mechanisms through which this phenomenon, also known as stress spillover, effects relationships are not completely clarified. Also, most of the studies utilized married couples, and less is known about stress spillover in dating relationships. The aim of this study was to investigate relations between external stress, relationship efficacy, and relationship satisfaction in dating relationships. A total number of 390 men and women, aged from 18 to 35 participated in the study. Our participants were dating for at least six months, but did not live with their partners. The results showed that experiencing greater levels of external stress was associated with lower relationship satisfaction. Both experienced external sources of stress and perceived distress significantly contributed to explaining relationship satisfaction. The results indicated that relationship efficacy mediateed the relationship between experienced and perceived stress and relationship satisfaction. Higher levels of experienced and perceived stress were associated with lower perception of relationship efficacy, which was related to lower relationship satisfaction. Our findings point to the importance of self-regulation processes for relationships outcomes in dating relationships in emerging adulthood. It seems that lower relationship efficacy partly explains the detrimental effects of external stress spillover on relationships.